GOLD RUSH DALAM SEJARAH AUSTRALIA - Sahl, Khansa Hasna; Ribawati, Eko (Cendikia: Jurnal Pendidikan dan Pengajaran, 2024)
Gold Rush is a term that refers to the massive and hasty movement of people to areas where gold has been discovered. The Gold Rush discussed in this research is the discovery of gold in New South Wales and Victoria which then gave rise to a very large flow of immigrants, especially immigrants from China to Australia. The research method used is historical research with descriptive qualitative source analysis. The data sources used are archives or official documents supported by book, journal and article sources. In this research we will find out what the Gold Rush is and how the Gold Rush occurs.